ANALISIS FAKTOR PENENTU DAYA SAING KOMODITAS PANGAN DI PROVINSI JAWA TENGAH - Harini, .; Purwaningsih, Yunastiti; Cahyadin, Malik; Widiyanti, Emi (EP FEB UNS, 2016)
This study identifies and analyzes competitiveness factors of food commodities in Central Java. The research data covers primary data with 245 respondents of food commodities sellers. The research method was using the Analytic Hierarchy Process (AHP). AHP calculation results show that food competitivesness factors involve: a) the agricultural sector investment with a value of 0.28; b) agricultural infrastructure with a value of 0.24; c) government program of food security and safety with a value of 0.20; d) government's active role in supervision of food with a value of 0.18; e) the accessibility of local food commodities with a value of 0.06; and f) the high demand for domestic food with a value of 0.05. Keywords: food commodities, competitiveness, AHP